ANALISIS URF TERHADAP URGENSI LABELISASI PARIWISATA HALAL SEBAGAI DAYA TARIK DESA WISATA DI PANTAI SIRING KEMUNING BANGKALAN MADURA: Mariatul Kiptiyah1, Ahmad Musadad2 - Kiptiyah, Mariatul (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
The halal tourism sector has now become a trend in global economic development which does not only offer places of worship at a tourist location. Madura is considered to have a very good development of the halal tourism industry because it has been known as an area that is closely related to Islamic nuances. Tourism Village is an independent living with the potential of the village as a tourist attraction, so each district needs to program a tourist village in order to increase it for the sake of increasing regional income and regional potential. Tourist villages usually fulfill all the elements of tourism that the attraction has. Among them are nature tourism, cultural tourism, and man-made tourism in a certain area supported by attractions, accommodation, and other facilities. This is in accordance with the local wisdom of the community. The tourist village, as a whole, includes all elements in the village to promote local wisdom and wisdom as tourism. This study aims to analyze the model of Islamic tourism that is spread in tourist villages in Bangkalan Regency. It is hoped that this Islamic tourism framework and model can be a reference in formulating innovations in world tourism governance so that the goals and targets desired by the Bangkalan Regency government can be implemented.